The mediating role of spirituality between self-value and counselling attitudes among Nigerian students in Malaysian universities - Idowu, G. T.; Hassan, Siti Aishah; Hamzah, Azimi; Baba, Maznah (REDSHINE Publication, 2016)
This study examined the mediating role of spirituality between self-value and counselling attitudes towards seeking professional psychological help among Nigerian students in Malaysian universities. The sample consisted of 394 Nigerian students who are currently enrolled in 10 randomly selected universities across Malaysia. They completed self-report questionnaires administered one-on-one in each of the selected institutions. It was hypothesized that there is no mediating relationship between self-value and counselling attitudes through spirituality. Two levels of quantitative research are presented: descriptive and correlational. SPSS version 22 and SEM analyses (descriptive statistics/AMOS) gave a contrary result, therefore the null hypothesis was rejected and it was concluded that spirituality mediated the relationship between self-value and counselling attitudes. Limitations in the current study, such as sample size, and directions for future studies to address the limitations are discussed.